Irving R. Kaufman papers - Kaufman, Irving R. (Irving Robert), 1910-1992.
Correspondence; memoranda; speeches; writings; case files, dockets, and opinions and other legal records; subject files; scrapbooks; photographs; and other papers chiefly documenting Kaufman's judicial career (1949-1992) on the U.S. District Court, Southern District of New York (1949-1961) and U.S. Court of Appeals, Second Circuit (1961-1992). Includes material on the espionage trial of Ethel and Julius Rosenberg (1953), the trial of reputed underworld figure Joseph Bonanno (1959), and the New Rochelle, N.Y., school desegregation case, Taylor v. Board of Education (1961). Other papers relate to the Juvenile Justice Standards Program and other American Bar Association committees on which Kaufman served. Correspondents include Warren E. Burger, Tom C. Clark, and Simon H. Rifkind.
Jurist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bonanno, Joseph, -- 1905-; Burger, Warren E., -- 1907-1995 -- Correspondence; Clark, Tom C. -- 1899-1977 -- Correspondence; Rifkind, Simon H. -- 1901- -- Correspondence; Rosenberg, Ethel, -- 1915-1953.; Rosenberg, Julius, -- 1918-1953.; American Bar Association; Juvenile Justice Standards Project; United States. -- Court of Appeals (2nd Circuit); United States. -- District Court (New York : Southern District); Appellate courts; Discrimination in education -- New York (State) -- New Rochelle; District courts -- New York (State); Judicial opinions -- United States; Juvenile justice, Administration of -- United States; Racketeering; Trials (Espionage) -- United States; Jurists